60 years of Rabinowicz’ criterion for adhesive wear - Elena Popova; Valentin L. Popov; Dae-Eun Kim (Friction)
Abstract 60 years ago, in 1958, Ernest Rabinowicz published a 5 page paper titled “The effect of size on the looseness of wear fragments” where he suggested a criterion determining the minimum size of wear particles. The criterion of Rabinowicz is based on the consideration of the interplay of elastic energy stored in “asperities” and the work of separation needed for detaching a wear particle. He was probably the first researcher who explicitly emphasized the role of adhesion in friction and wear. In a recent paper in Nature Communications, Aghababaei, Warner and Molinari confirmed the criterion of Rabinowicz by means of quasi-molecular dynamics and illustrated the exact mechanism of the transition from plastic smoothing to formation of wear debris. This latter paper promoted the criterion of Rabinowicz to a new paradigm for current studies of adhesive wear. The size arguments of Rabinowicz can be applied in the same form also to many other problems, such as brittle-ductile transition during indentation, cutting of materials or ultimate strength of nano-composites.